3D dose reconstruction based on in vivo dosimetry for determining the dosimetric impact of geometric variations in high-dose-rate prostate brachytherapy. (June 2022) - Jørgensen, Erik B.; Buus, Simon; Bentzen, Lise; Hokland, Steffen B.; Rylander, Susanne; Kertzscher, Gustavo; Beddar, Sam; Tanderup, Kari; Johansen, Jacob G.
Highlights: 3D dose reconstruction based on in vivo dosimetry was performed for high-dose-rate prostate BT. Maximum relative deviation in the clinical target volume D 90% was 5%. In one fraction a 18% increase in bladder D 2cm 3 was observed and a maximum deviation of 15% in urethra dose. 3D dose reconstruction can aid in determining the dosimetric impact of geometric variations in BT. Abstract: Introduction: In vivo dosimetry (IVD) can be used for source tracking (ST), i.e., estimating source positions, during brachytherapy. The aim of this study was to exploit IVD-based ST to perform 3D dose reconstruction for high-dose-rate prostate brachytherapy and to evaluate the robustness of the treatments against observed geometric variations. Materials and Methods: Twenty-three fractions of high-dose-rate prostate brachytherapy were analysed. The treatment planning was based on MRI. Time-resolved IVD was performed using a fibre-coupled scintillator. ST was retrospectively performed using the IVD measurements. The ST identified 2D positional shifts of each treatment catheter and thereby inferred updated source positions. For each fraction, the dose was recalculated based on the source-tracked catheter positions and compared with the original plan dose using differences in dose volume histogram indices. Results: Of 352 treatment catheters, 344 had shifts of less than 5 mm. Shifts between 5 and 10 mm were observed for 3 catheters, and shifts greater than 10 mm for 2 catheters. The ST failed for 3 catheters. The maximum relative difference in clinical target volume (prostate + 3 mm isotropic margin) D 90% was 5%. In one fraction, the bladder D 2cm 3 dose increased by 18% (1.4 Gy) due to a single source position being inside the bladder rather than nearby as planned. The max increase in urethra dose was 1.5 Gy (15%). Conclusion: IVD-based 3D dose reconstruction for high-dose-rate prostate brachytherapy is feasible. The dosimetric impact of the observed catheter shifts was limited. Dose reconstruction can therefore aid in determining the dosimetric impact of geometric variations and errors in brachytherapy.